Drug utilization pattern of psychotropic medicines in tertiary care centre of Bastar Region, Chhattisgarh, India - Agrawal, Ratna; A., Marium K.; Sharma, Raj Kumar; Sharma, Sanat Kumar; Jaiswal, Mahendra Kumar (International Journal of Basic & Clinical Pharmacology, 2019)
Background: With the changing lifestyle, the incidence of psychiatric illness is increasing day by day. And the mental illnesses not only affect the social and personal life but also adds additional economic burden affecting quality of life of the person. So, proper diagnosis and management of psychiatric illnesses is utmost important. So, keeping this in mind, the present study has been conducted to evaluate drug utilization pattern of psychotropic medicines in tertiary care centre of Bastar region. Methods: After obtaining approval from Institutional Ethics Committee, present study was conducted in 237 patients for a period of 3 months from February 2019 to April 2019. The data of patients attending psychiatry OPD was collected in a structured case record form. The data were analysed using graph pad prism version 6.0. Results: Out of total 237 patients, males 136(57.38%) outnumbered females 101 (42.62%). The major psychiatric illness reported was schizophrenia (45.99%) followed by bipolar affective disorder (16%) and generalized anxiety disorder (14.35%). Average number of psychotropic drugs per prescription was 1.74±1.02. The percentage of drugs prescribed from state Essential drug List (EDL) was 93.05%. Conclusions: Overall, the principles of rational prescribing was tried to be maintained, as polypharmacy has been avoided and most of the drugs were prescribed from the state EDL. The use of generic drugs should be increased to make prescriptions more rational and to cut down the cost of the therapy which may be helpful in increasing the quality of life of the patients.